Different mechanisms in weight loss-induced blood pressure reduction between a calorie-restricted diet and exercise - Masuo, Kazuko; Rakugi, Hiromi; Ogihara, Toshio; Lambert, Gavin W (Hypertension research, 2012)
The present study compared the effectiveness of a mild calorie-restricted diet (D) alone, exercise (EX) alone and a combination of D+EX on weight loss-induced blood pressure (BP) reduction over 24 weeks. We focussed especially on the relationship between sympathetic nervous activity, as indicated from measures of plasma norepinephrine (NE), and insulin resistance (homeostasis model of insulin resistance, HOMA-IR). The three groups each comprised 30 obese, hypertensive men. Body mass index (BMI), fat mass, waist-to-hip ratio, BP, plasma NE and HOMA-IR were measured every 2 weeks during the first 4 weeks and subsequently every 4 weeks for the next 20 weeks. All basal parameters were similar among the three groups. At 24 weeks, the combination group with D+EX comprised a significantly higher prevalence of normotensive subjects than the D alone or EX alone group ( P <0.05). In the D alone group, plasma NE was decreased significantly at 2 weeks, reductions in BMI, fat mass and BP were observed at 8 weeks, and waist-to-hip ratios and HOMA-IR were decreased at 12 weeks. In comparison, in the EX alone group, significant reductions of fat mass and HOMA-IR were observed at 4 weeks. Plasma NE and HOMA-IR were reduced at 8 weeks while decreases in BP were detected at 12 weeks. In the D+EX group, significant reductions in plasma NE were observed at 2 weeks followed by significant decreases in BMI, fat mass, waist-to-hip ratio, BP levels and HOMA-IR at 4 weeks. The magnitudes of reductions of all parameters were greatest in the D+EX group. These results demonstrate that D+EX exerts a stronger ameliorative effect on weight loss, weight loss-induced BP reduction, normalization of BP, sympathetic activation and insulin resistance compared with D or EX alone. D and EX might, perhaps, exert different mechanisms on weight loss and weight loss-induced BP reduction; however, a combination of caloric restriction and exercise is preferred to control BP levels in obese hypertensive patients.